2014
DOI: 10.1152/ajprenal.00352.2013
|View full text |Cite
|
Sign up to set email alerts
|

ROS dependence of cyclooxygenase-2 induction in rats subjected to unilateral ureteral obstruction

Abstract: Østergaard M, Christensen M, Nilsson L, Carlsen I, Frøkiaer J, Nørregaard R. ROS dependence of cyclooxygenase-2 induction in rats subjected to unilateral ureteral obstruction. Am J Physiol Renal Physiol 306: F259 -F270, 2014. First published November 13, 2013 doi:10.1152/ajprenal.00352.2013.-Oxidative stress resulting from unilateral ureteral obstruction (UUO) may be aggravated by increased production of ROS. Previous studies have demonstrated increased cyclooxygenase (COX)-2 expression in renal medullary int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 36 publications
3
27
1
Order By: Relevance
“…Recent studies have shown that ROS also plays a role in the UUO rat mode. 17 Our study also showed a significant increase in the amount of ROS in the kidneys of the UUO group compared to the sham group. MDA is the product of oxidative stress in vivo, which can reflect the level of oxidative stress.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Recent studies have shown that ROS also plays a role in the UUO rat mode. 17 Our study also showed a significant increase in the amount of ROS in the kidneys of the UUO group compared to the sham group. MDA is the product of oxidative stress in vivo, which can reflect the level of oxidative stress.…”
Section: Discussionsupporting
confidence: 67%
“…Reactive oxygen species (ROS) plays an important role as a key signalling molecule in the progress of interstitial fibrosis and epithelial‐mesenchymal transition (EMT). Recent studies have shown that ROS also plays a role in the UUO rat mode . Our study also showed a significant increase in the amount of ROS in the kidneys of the UUO group compared to the sham group.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, we may have been able to detect anti-apoptotic effects in a more chronic obstruction model, but further studies would be needed to test this. Antioxidants can ameliorate UUO-associated injury, as we have previously demonstrated that the antioxidants NADPH oxidase inhibitor diphenyleneiodonium (DPI) and the complex I inhibitor rotenone (ROT) prevented renal damage in response to 3dUUO42. Our current data suggest that metformin can upregulate NQO1 and HO-1, which might reduce ROS in response to obstructive nephropathy.…”
Section: Discussionsupporting
confidence: 57%
“…DRI may also provide additional protection over other RAS inhibitors by interfering with the enhanced catalytic activity of (pro)renin after the binding of these molecules to the (pro)renin receptor (43). Further investigations are needed to clarify whether various potential signaling pathways, as seen in a recent study [e.g., cyclooxygenase-PGE 2 and ROS (38)] are involved in AQP2 regulation after UUO in response to DRI, ARB, or ACE inhibitor. A very recent study (13), however, showed that in contrast to an ACE inhibitor, aliskiren partitions to and is retained in kidneys, where aliskiren was found to localize not only in afferent arteries but also in the distal nephron and collecting ducts (13).…”
Section: Discussionmentioning
confidence: 97%